STRATEGI PAK DALAM MEMBENTUK KARAKTER KRISTIANI BERDASARKAN TEORI IMAN JAMES FOWLER BAGI ANAK USIA SEKOLAH DI ERA DIGITAL - Simanjuntak, Bonar Dominggos; Liud, Yahya Herman; Legi, Ribka Esther (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
Children aged 6-12 in the digital era face many problems, including social media addiction, cyberbullying, identity crisis, social pressure, lack of direct interaction, online hoaxes, privacy exploitation, decreased concentration in learning, and social anxiety. Digitalization shapes character and mental health, but it also has disadvantages. The main problem is when they don't want to go to church and the tendency to play online games. Seeing the reality or the main problem, this article will present how the opportunities and methods used with Christian religious education strategies in shaping the Christian character of adolescents in the digital era. The purpose of this article is to analyze the extent to which Christian religious education strategies shape the character of children aged 6-12 years in the digital era which have a positive impact on the development of adolescent character according to the expectations of parents, families and churches, then it will be analyzed using James Fowler's Faith theory. The method that the author will use is library research explaining how Christian religious education strategies shape the character of adolescents in the digital era. The research results show that collaboration between parents, churches and schools has a significant impact on shaping the character of adolescents based on Christian values, and how Christian religious education strategies in the digital era can be internalized with Christian-based character values.